A rare cause for osteonecrosis of femoral head and peripheral nerve damage of a child with depression - Ke Wang; Yun Chen; Hao Zhou (BMC Musculoskeletal Disorders)
Abstract Background Avascular necrosis of the femoral head (ANFH) that is due to the use of carbamazepine (CBZ) in children whose condition requires long-term oral CBZ is relatively rare, and there are no clinical reports on this topic. Herein, we present a rare case of femoral head necrosis and peripheral nerve damage due to long-term use of CBZ in a child with depression. Patient presentation A 12-year-old boy who was taking oral CBZ for depression presented to the hospital with a sudden onset of impaired consciousness. On admission, the blood CBZ concentration was 32.6 µg/mL, an electromyogram (EMG) revealed severe partial injury to the left common peroneal and tibial nerves, and magnetic resonance imaging (MRI) of the hip revealed necrosis of the left femoral head. On predischarge evaluation, the CBZ blood level was < 0.2 µg/mL. The long-term use of CBZ is thought to have resulted in femoral head necrosis and peripheral nerve damage. Conclusions To our knowledge, this is the first literature report of femoral head necrosis with peripheral nerve damage due to long-term CBZ use. For patients receiving long-term treatment with CBZ, careful monitoring for osteoarthritis, bone pain, and decreased sensation and range of motion of the extremities, as well as detailed medical history-taking and complete imaging, electromyography, and neurosonography of the hip joint, are needed.